Turkish Journal of Urology 2022
DOI: 10.5152/tud.2022.22132
|View full text |Cite
|
Sign up to set email alerts
|

AHNAK2 Urinary Protein Expression as Potential Biomarker for Bladder Cancer Detection: A Pilot Study

Abstract: Objective: This study aimed to measure the AHNAK2 urinary levels in bladder cancer patients. Material and methods: This prospective case–control study enrolled 67 participants between January and March 2019 and were categorized into bladder cancer group (n = 37), with histologically proven bladder cancer, and control group (n = 30), with histologically verified benign lesions or with no bladder cancer indication during follow-up. Urine samples of 15 mL were collected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…collected urine samples from 67 cancer patients with bladder occupancy (bladder cancer group N=37, benign bladder tumors N=30) and found that the mean urinary AHNAK2 protein level was almost 10 times higher in bladder cancer patients than that in controls (49.08 pg/mL vs. 5.28 pg/mL) and that AHNAK2 expression level in invasive bladder cancer was significantly higher than that in non-invasive bladder cancer (117.99 pg/mL vs. 7.14 pg/mL). Similarly, AHNAK2 level was significantly higher in muscle-invasive bladder cancer than that in non-muscle-invasive bladder cancer (160.05 pg/mL vs. 23.19 pg/mL) ( 102 ). A large sample analysis using the TCGA and GEO databases has been reported to confirm that AHNAK2 is overexpressed in bladder cancer and is associated with poorer overall survival ( 103 ).…”
Section: Relationship Between Ahnak Family and Tumor Developmentmentioning
confidence: 99%
“…collected urine samples from 67 cancer patients with bladder occupancy (bladder cancer group N=37, benign bladder tumors N=30) and found that the mean urinary AHNAK2 protein level was almost 10 times higher in bladder cancer patients than that in controls (49.08 pg/mL vs. 5.28 pg/mL) and that AHNAK2 expression level in invasive bladder cancer was significantly higher than that in non-invasive bladder cancer (117.99 pg/mL vs. 7.14 pg/mL). Similarly, AHNAK2 level was significantly higher in muscle-invasive bladder cancer than that in non-muscle-invasive bladder cancer (160.05 pg/mL vs. 23.19 pg/mL) ( 102 ). A large sample analysis using the TCGA and GEO databases has been reported to confirm that AHNAK2 is overexpressed in bladder cancer and is associated with poorer overall survival ( 103 ).…”
Section: Relationship Between Ahnak Family and Tumor Developmentmentioning
confidence: 99%